5G, and technologies that will make it happen (International Journal of Scientific Research and Management (IJSRM), 2018)
The next generation of wireless networks are already being deployed in advanced markets. This 5th generation wireless technology promises to improve network performance by factors of 10-1000’s, thus providing unlimited potential in consumer and enterprise segments. In this paper, I will try to explain how 5G aims to reach its planned capabilities through use of new technologies such as mmWave, Network Virtualization, Edge computing and Network Slicing